Nuevos nidos de aves argentinas: Muscisaxicola rufivertex, Catamenia inornata, Sicalis olivascens y Carduelis crassirostris - Salvador, Sergio A.; Narosky, Samuel (El Hornero, 1983)
Este artículo no cuenta con un resumen.